APS: High-Energy X-rays Expediting Applied and Fundamental Research. Issue 6 (1st December 2020) - Ruett, U.; Almer, J.; Kenesei, P.; Park, J.-S; Osborn, R.; Ren, Y.; Robinson, D.; Krogstad, M.; Rosenkranz, S.; Zhang, Xuan; Li, Meimei; Wiaderek, K.M.
Abstract : The Advanced Photon Source (APS) at Argonne National Laboratory (ANL) was designed and built as one of the first large third-generation synchrotrons operated at 7 GeV. The United States Department of Energy (DOE) Office of Science funded the construction and continues to fund the operation of this national facility. The beamlines were originally operated by Collaborative Access Teams (CAT), which allowed a strong involvement of research institutes, universities, and industry. Today, 43 of 68 beamlines are operated by the X-ray Science Division (XSD), and 35 beamlines are directly funded by the DOE Office of Science. The APS became operational in 1995 and was planned right from the beginning with four beamlines dedicated to high-energy X-rays above 40 keV: 1-ID designed to study engineering materials science, 6-ID-D for magnetism and condensed matter research, 11-ID-B dedicated to magnetic Compton scattering using an Elliptical Multipole Wiggler, and 11-ID-C for materials science and condensed matter physics. These stations were later joined by the bending magnet beamlines 6-BM for white beam studies and 17-BM for rapid powder diffraction. CAT operated beamlines such as 15-ID for crystallography or 16-ID for high-pressure studies, which also use the high-energy X-ray regime frequently. The program in Compton scattering ended in 2004, and the wiggler was replaced by an undulator. 11-ID-B became the first dedicated station for Pair Distribution Function (PDF) Analysis.